2020
DOI: 10.4049/jimmunol.1900240
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Trap–Associated CEACAM1 as a Putative Therapeutic Target to Prevent Metastatic Progression of Colon Carcinoma

Abstract: Neutrophils promote tumor growth and metastasis at multiple stages of cancer progression. One mechanism through which this occurs is via release of neutrophil extracellular traps (NETs). We have previously shown that NETs trap tumor cells in both the liver and the lung, increasing their adhesion and metastasis following postoperative complications. Multiple studies have since shown that NETs play a role in tumor progression and metastasis. NETs are composed of nuclear DNA-derived web-like structures decorated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 51 publications
(62 reference statements)
1
53
0
Order By: Relevance
“…Of these 84 genes, 16 genes were NETs associated genes ( Figure 5B; Table 3) (33-46) Of the 16 genes, LGALS9, HCK, LCP1, CEACAM1 were involved in the cytokine-mediated signaling pathway. S100A8, LGALS9, and CTSC were involved in regulation of apoptotic signal by enrichment annotation from the Metascape tool ( Figure 5B; Table 3) (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Neutrophil Activation Related Genes Enrichment Analysismentioning
confidence: 99%
“…Of these 84 genes, 16 genes were NETs associated genes ( Figure 5B; Table 3) (33-46) Of the 16 genes, LGALS9, HCK, LCP1, CEACAM1 were involved in the cytokine-mediated signaling pathway. S100A8, LGALS9, and CTSC were involved in regulation of apoptotic signal by enrichment annotation from the Metascape tool ( Figure 5B; Table 3) (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Neutrophil Activation Related Genes Enrichment Analysismentioning
confidence: 99%
“…Related factors released by neutrophils, such as interleukin (IL)-17, can promote the EMT process of tumor cells via the JAK2/STAT3 pathway ( 24 ). NETs have been reported to be able to promote tumor cell adhesion and thus promote tumor cell progression and metastasis ( 25 ). In the present study, a large amount of NETs formation was found in the plasma of patients with advanced GC and in GC tumor tissues; however, the interaction between tumor and NETs needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…P ≤ 0.05 was considered statistically significant, and P ≤ 0.01 as highly significant. Pearson correlation coefficient lower than 0.4 indicates poor reproducibility, which range from 0.4–0.75, denoting fair reproducibility, and equal to 0.75 indicates good reproducibility 17 . ( M represents the median of the data).…”
Section: Methodsmentioning
confidence: 99%